Synthesis and Atimicrobial Evaluation of Deuterated Analogues of Metronidazole - Anjana G V (Iraqi Journal of Pharmaceutical Sciences, 2022)
The discovery of novel therapeutic molecules is always difficult, and there are a variety of methodologies that use the most diverse and innovative medicinal chemistry approaches. One such approach is the deuteration technique: Deuteration is the process of substituting deuterium for hydrogen in a molecule. When compared to the drug molecule, its deuterated analogues may retain the features of the original molecule and, in some cases, improve its pharmacological activity, with fewer side effects and lower toxicity. Metronidazole is a commonly used antibiotic to treat anaerobic bacterial infections, protozoal and microaerophilic bacterial infections. Metronidazole has a half-life of 6.5 ± 2.9 hours. A number of studies have recently been conducted on the selective substitution of hydrogen with deuterium. which increases the bond strength, increasing the biological half-life and, consequently, the drug's metabolic stability also increases. In an attempt to address metronidazole's drawbacks and clinical resistance, deuterated metronidazole was synthesised, characterised, and tested for antibacterial, antifungal, and anti-tubercular activities. The metronidazole and its deuterated compound showed equipotent antifungal activity and aerobic antibacterial activity. Also, when compared with the non-deuterated compound, deuterated metronidazole exhibited better anaerobic antibacterial and anti-tubercular activity.